2023
DOI: 10.1097/md.0000000000033965
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of diabetic kidney disease and autophagy: A review

Jiawei Yu,
Yan Liu,
Hongjie Li
et al.

Abstract: Diabetic kidney disease (DKD) is one of the main complications of diabetic microangiopathy. The pathogenesis of DKD is very complex, including autophagy, inflammation, oxidative stress. Although a series of treatment intervention have achieved certain results in the treatment of diabetic nephropathy, still cannot reverse the kidney injury of diabetic nephropathy. The kidney is one of the most important organs of energy metabolism. Renal function is highly dependent on phagocytosis of mitochondria, and aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…This regulation can lead to a downregulation of NOS, a key factor in maintaining vascular endothelial relaxation, and an upregulation of endothelin 1, which contributes to vascular endothelial contraction. Moreover, PKC activation can also enhance the expression of collagen fibers and proinflammatory factors, ultimately expediting renal fibrosis [128,129]. This process is facilitated by transcription factor β, plasminogen activator inhibitor 1 (PAI-1), and NF-κB.…”
Section: Activation Of the Protein Kinase C (Pkc) Pathwaymentioning
confidence: 99%
“…This regulation can lead to a downregulation of NOS, a key factor in maintaining vascular endothelial relaxation, and an upregulation of endothelin 1, which contributes to vascular endothelial contraction. Moreover, PKC activation can also enhance the expression of collagen fibers and proinflammatory factors, ultimately expediting renal fibrosis [128,129]. This process is facilitated by transcription factor β, plasminogen activator inhibitor 1 (PAI-1), and NF-κB.…”
Section: Activation Of the Protein Kinase C (Pkc) Pathwaymentioning
confidence: 99%
“…Autophagy is an intracellular pathway that maintains cellular homeostasis by degrading cytoplasmic components via autolysosome formation of autolysosomes (135). Studies have shown that the development of DKD is associated with defective renal autophagy (119,(136)(137)(138)(139)(140). In DKD, the microtubuleassociated protein 1A/1b-light chain 3 (LC3-II) is dependent on phagocytosis of endoplasmic reticulum membranes to form lipid autophagosomes, which with their cargoes, mainly composed of ChE and TG, fuse with lysosomes to form autophagic lysosomes, in which the cargo is degraded to produce FAs, a process known as lipophagy (141-147).…”
Section: Lipophagymentioning
confidence: 99%